High-entropy alloy nanoflower array, preparation method thereof and application of high-entropy alloy nanoflower array as electrode material
By growing high-entropy alloy nanoflower array materials on foamed cobalt substrates, the problems of poor catalytic performance and easy shedding in the electrolytic hydrogen production system are solved, efficient catalysis and stability are improved, and the cost of hydrogen production is reduced .
Patent Information
- Application Number
- CN202411480405.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-23
AI Technical Summary
In the electrolytic hydrogen production system, the catalytic performance of the two poles of the existing catalysts is poor, making it difficult to achieve efficient hydrogen production, and the powdered catalyst is prone to fall off, affecting the catalytic performance.
Using high-entropy alloy nanoflower array material, the porous array electrode is formed by growing in situ on the foamed cobalt substrate to ensure that the catalyst is in close contact with the substrate, providing rich active sites and large specific surface area, and promoting charge transfer and gas release.
High-efficiency catalytic hydrogen evolution reaction and hydrazine oxidation reaction are achieved, which reduces power costs, improves the stability and mass transfer efficiency of the catalyst, and is at a low cost.
Smart Images

Figure CN119307958A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high entropy alloy catalysts, and in particular relates to a high entropy alloy nanoflower array, a preparation method thereof and an application thereof as an electrode material. Background Art
[0002] Hydrogen is considered to be one of the most promising alternative energy sources for the next generation due to its extremely high mass energy density, zero carbon emissions and renewable advantages. Hydrogen production by water electrolysis decomposes water into hydrogen and oxygen. It has attracted widespread attention due to the high purity of the hydrogen produced and the lack of large amounts of CO2 emissions. Since hydrogen production by water electrolysis consists of two important half-reactions, oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), OER is a relatively complex four-electron transfer process with slow reaction kinetics and a theoretical potential as high as 1.23V, which leads to high electricity costs, so its large-scale application is limited. In recent years, studies have shown that replacing OER with thermodynamically more favorable small molecule oxidation reactions can greatly reduce the hydrogen production voltage, save energy consumption, and have great application value (Adv. Mater. 2024, 36, 2309715). Among them, the hydrazine oxidation reaction (HzOR) has a low theoretical voltage of -0.33V and has been proven to be a promising strategy to replace anode OER and achieve low-pressure and efficient hydrogen production. In particular, compared with pure water electrolysis systems, hydrazine oxidation-assisted hydrogen production (OHzS) systems can effectively save more than half of the electrical energy, and because the byproduct is N2 instead of O2, it is safer. However, the catalysts currently used in OHzS systems have simple compositions and structures and poor intrinsic activity, making it difficult to simultaneously and efficiently catalyze the anionic and cation-based reactions of the OHzS system. Therefore, it remains a huge challenge to prepare catalysts or electrode materials that can efficiently catalyze the OHzS system and achieve industrial-grade current density hydrogen production.
[0003] High entropy alloy (HEA) catalysts have attracted extensive attention due to their remarkable catalytic properties. Currently, most studies focus on powdered HEA catalysts, which need to be coated on a conductive substrate for subsequent catalytic reactions. However, the powder material easily falls off the conductive substrate, resulting in a decrease in catalytic performance. In contrast, the self-supporting array electrode formed by in-situ growth of the catalyst on the conductive substrate can not only ensure close contact between the catalyst and the substrate and prevent the catalyst from falling off during the electrocatalytic process, but also promote rapid charge transfer, provide a larger specific surface area and abundant active sites. In addition, the porous array electrode can also promote the diffusion of electrolytes and the rapid release of generated gases, thereby improving the overall mass transfer efficiency of the catalyst. However, due to the different physicochemical properties of different metals, especially the different nucleation / growth kinetics of various metals in HEA, the precise preparation of high entropy alloy nanosheets or nanoflower array materials with a homogeneous phase structure remains a huge challenge.
[0004] In order to solve the above problems, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a high entropy alloy nanoflower array and a preparation method thereof, which can efficiently catalyze hydrogen evolution reaction, hydrazine oxidation reaction and hydrazine oxidation-assisted hydrogen production system, and has high practical application value.
[0006] The first aspect of the present application provides a high entropy alloy nanoflower array material, the high entropy alloy nanoflower array material comprising: a foam cobalt substrate and a high entropy alloy nanoflower array loaded on the foam cobalt substrate, the high entropy alloy nanoflower array consisting of five metal elements: Co, Ni, Mo, Zn, and Cu;
[0007] In the high entropy alloy nanoflower array, the atomic percentages of Co atoms, Ni atoms, Mo atoms, Zn atoms and Cu atoms are all 0.5% to 60%.
[0008] Preferably, the high entropy alloy nanoflower array is composed of a plurality of two-dimensional nanosheets, the plurality of two-dimensional nanosheets have different orientations, and the two-dimensional nanosheets are perpendicular to the foam cobalt substrate.
[0009] The second aspect of the present application provides a method for preparing the high entropy alloy nanoflower array material according to the first aspect, comprising the following steps:
[0010] Step a, placing a water-soluble molybdenum salt and a precipitant in a reaction container, adding water and dissolving them to obtain a first mixed solution;
[0011] Step b, adding a water-soluble cobalt salt, a water-soluble nickel salt, a water-soluble copper salt, and a water-soluble zinc salt to the first mixed solution, mixing to obtain a second mixed solution;
[0012] Step c, placing the foamed cobalt into the above reaction container, sealing the reaction container, and reacting the reaction container at 80-120° C. for 8-12 hours to obtain a foamed cobalt-loaded high entropy alloy nanoflower array precursor;
[0013] Step d, placing the reducing agent and the cobalt foam-loaded high entropy alloy nanoflower array precursor obtained in step c into a reaction container, sealing the reaction container, and reacting at 140-160° C. for 8-12 hours to obtain a cobalt foam-loaded high entropy alloy nanoflower array.
[0014] Preferably, the water-soluble molybdenum salt in step a is (NH4)6Mo7O 24 ·4H2O, the precipitant is CO(NH2)2.
[0015] Preferably, in step d, the reducing agent is an ethylene glycol solution containing sodium borohydride and sodium hydroxide, wherein the concentration of sodium hydroxide in the ethylene glycol solution is 0.3-0.8 mol / L, and the concentration of sodium borohydride in the ethylene glycol solution is 0.03-0.07 mol / L.
[0016] Preferably, the mass ratio of the sodium borohydride to the high entropy alloy nanoflower array precursor is 1:1.5.
[0017] Preferably, in the first mixed solution, the concentration of the water-soluble molybdenum salt is 0.01-0.03 mol / L, and the concentration of the precipitant is 0.25-0.45 mol / L.
[0018] Preferably, the amount of the water-soluble cobalt salt, water-soluble nickel salt, water-soluble zinc salt, and water-soluble copper salt added to the first mixed solution has a molar volume ratio of 0.02-0.04 mol / L, 0.025-0.04 mol / L, 0.01-0.02 mol / L, and 0.004-0.02 mol / L.
[0019] The third aspect of the present application provides the use of the high entropy alloy nanoflower array material described in the first aspect for catalyzing hydrogen evolution reaction.
[0020] The fourth aspect of the present application provides the use of the high entropy alloy nanoflower array material described in the first aspect for catalyzing hydrazine oxidation reaction.
[0021] The fifth aspect of the present application provides the use of the high entropy alloy nanoflower array material described in the first aspect as a cathode and / or anode material for a hydrazine oxidation-assisted hydrogen production system.
[0022] The present invention has the following beneficial results:
[0023] (1) The present invention prepares a high entropy alloy nanoflower array for the first time, and realizes the controllable synthesis of a high entropy alloy nanoflower array with a uniform phase. At the same time, the preparation method of the present invention is simple, and the elements used are all non-precious metal elements, thereby greatly reducing the preparation cost;
[0024] (2) The high entropy alloy nanoflower array prepared by the present invention has multiple components, realizes the construction of multiple active sites, and has an adjustable electronic structure, thus showing excellent catalytic performance in hydrogen evolution reaction, hydrazine oxidation reaction and hydrazine oxidation-assisted hydrogen production system as well as extremely excellent stability.
[0025] (3) The present application unexpectedly discovered that, compared with other foam metal substrates, such as nickel foam, the high entropy alloy nanoflower array prepared by the present invention has a higher loading amount on the cobalt foam substrate, thereby providing a larger electrochemically active specific surface area, exposing more active sites and more complete contact with the electrolyte.
[0026] (4) The array prepared by the present invention is in close contact with the substrate, promoting rapid charge transfer and effectively preventing the catalyst from falling off during the electrocatalytic process, especially at industrial-grade high current density. In addition, it has super-gas-repellent properties, which can promote the diffusion of electrolytes and the rapid release of generated gases, thereby improving the overall mass transfer efficiency and having strong practical applicability.
[0027] (5) The method of the present invention can be used to form a uniformly distributed high entropy alloy nanoflower array for any combination of metal types that are not random. The present invention specifically selects five metals, Co, Ni, Mo, Zn, and Cu, and unexpectedly finds that they can form a high entropy alloy nanoflower array with uniform element distribution, and unexpectedly finds that they have excellent performance as catalysts for hydrogen evolution reaction and hydrazine oxidation reaction. Among them: Zn and Cu metal elements are rarely used as materials for hydrogen evolution reaction, but in the materials of the present invention, Zn and Cu can play the role of regulating the electronic structure of other metals, increasing the entropy value and stability of the system. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image (SEM) of the NiCoMoZnCu high entropy alloy nanoflower array supported by foam cobalt obtained in Example 1.
[0029] Figure 2 This is a high-resolution transmission electron microscopy image (HRTEM) of the NiCoMoZnCu high-entropy alloy nanoflower array obtained in Example 1.
[0030] Figure 3 This is the X-ray diffraction (XRD) pattern of the NiCoMoZnCu high entropy alloy nanoflower array obtained in Example 1.
[0031] Figure 4 This is an atomic structure characterization diagram of the NiCoMoZnCu high entropy alloy nanoflower obtained in Example 1.
[0032] Figure 5 This is the element distribution map (Mapping) of the NiCoMoZnCu high entropy alloy nanoflower obtained in Example 1.
[0033] Figure 6 This is the result of inductively coupled plasma elemental analysis (ICP) of the NiCoMoZnCu high entropy alloy nanoflower array obtained in Example 1.
[0034] Figure 7 a and b Linear voltammetry (LSV) test curves of the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 1, the cobalt foam substrate of Example 1 and commercial Pt / C as electrode materials for hydrogen evolution reaction and hydrazine oxidation reaction.
[0035] Figure 8 The double layer capacitance (C) of NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 1 and commercial Pt / C as electrode materials at different scan rates dl )value
[0036] Fig. 9 a and b are the Nyquist curves of the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 1, the cobalt foam substrate of Example 1 and commercial Pt / C for hydrogen evolution reaction and hydrazine oxidation reaction.
[0037] Fig.10 a and b are the chronoamperometric curves (it) of the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 1 and commercial Pt / C for hydrogen evolution reaction and hydrazine oxidation reaction.
[0038] Fig.11 a and b are the LSV performance comparisons of the OHzS and OWS systems composed of various electrodes, and the electrolytes used are 1.0 mol / L potassium hydroxide solution containing 0.2 mol / L hydrazine hydrate (N2H4) and 1.0 mol / L potassium hydroxide solution, respectively.
[0039] Fig.12 This is the chronoamperometric curve (it) of the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained in Example 1 for the OHzS system.
[0040] Fig.13 This is a high-resolution transmission electron microscopy image (HRTEM) of the NiCoMoZnCu high-entropy alloy nanoflower array obtained in Example 2.
[0041] Fig.14 This is the element distribution map (Mapping) of the NiCoMoZnCu high entropy alloy nanoflower obtained in Example 2.
[0042] Fig.15 These are the results of inductively coupled plasma elemental analysis (ICP) of the NiCoMoZnCu high entropy alloy nanoflower array obtained in Example 2.
[0043] Fig.16 a and 16b are the linear voltammetry (LSV) test curves of the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 2 as electrode material for hydrogen evolution reaction and hydrazine oxidation reaction.
[0044] Fig.17 This is a scanning electron microscope image (SEM) of the NiCoMoZnCu high entropy alloy nanoflower array supported by foam cobalt obtained in Example 3.
[0045] Fig.18 a and 18b are the linear voltammetry (LSV) test curves of the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 3 as electrode material for hydrogen evolution reaction and hydrazine oxidation reaction.
[0046] Fig.19 This is a scanning electron microscope image (SEM) of the NiCoMoZnCu high entropy alloy nanoflower array supported by foam cobalt obtained in Example 4.
[0047] Fig. 20 20a and 20b are the linear voltammetry (LSV) test curves of the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 4 as an electrode material for hydrogen evolution reaction and hydrazine oxidation reaction.
[0048] Fig.21 These are the linear voltammetry (LSV) test curves of the catalytic material obtained in Example 1 and the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 1 for hydrogen evolution reaction.
[0049] Fig. 22 This is a scanning electron microscope (SEM) image of the catalytic material obtained in Comparative Example 2.
[0050] Fig.23 This is a linear voltammetry (LSV) test curve of the catalytic material obtained in Example 3 and the NiCoMoZnCu high entropy alloy nanoflower array supported by foam cobalt obtained in Example 1 for hydrogen evolution reaction. DETAILED DESCRIPTION
[0051] The present invention will be further described below in conjunction with specific embodiments. These specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0052] Example 1
[0053] The high entropy alloy nanoflower array material is prepared by the following steps:
[0054] Step a: (NH4)6Mo7O 24 4H2O and CO(NH2)2 were placed in a 100mL reactor, 40mL of deionized water was added and ultrasonically dissolved to obtain a first mixed solution such that in the first mixed solution, (NH4)6Mo7O 24 The concentration of 4H2O is 0.03 mol / L, and the concentration of CO(NH2)2 is 0.45 mol / L.
[0055] Step b, add Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O to the first mixed solution, mix by ultrasonic, and obtain a second mixed solution; the molar volume ratio of the water-soluble cobalt salt, water-soluble nickel salt, water-soluble copper salt, and water-soluble zinc salt to the first mixed solution is: 0.04 mol / L, 0.04 mol / L, 0.02 mol / L, 0.02 mol / L. .
[0056] Step c, place a 2cm×4cm cobalt foam in 40mL of 6 mol / L HCl solution, ultrasonically treat for 3min, then use deionized water and ethanol to ultrasonically clean the cobalt foam three times, then blow dry the cobalt foam, put it into the above-mentioned 100mL reactor, immerse it completely in the solution, close the reactor, move the reactor into a blast oven, and react at 120°C for 12h. After the reaction is completed, take out the cobalt foam with the sample, use deionized water and ethanol to ultrasonically clean it three times, put it into a blast oven after cleaning, and dry it at 80°C for 8h to obtain 0.15g NiCoMoZnCu high entropy alloy nanoflower array precursor loaded with cobalt foam;
[0057] Step d, pour 36mL of ethylene glycol solution containing 0.07 mol / L sodium borohydride and 0.8 mol / L sodium hydroxide into a 50mL reactor, and then put 0.15g of high entropy alloy nanoflower array precursor loaded with cobalt foam obtained in step c into the reactor (the mass ratio of the sodium borohydride to the high entropy alloy nanoflower array precursor is 1:1.5), so that it is completely immersed in the solution, the reactor is closed, and the reactor is moved into a blast oven and reacted at 160°C for 12h. After the reaction is completed, take out the reduced sample, use deionized water and ethanol to ultrasonically clean it three times, and after cleaning, put it into a vacuum drying oven and dry it at 60°C for 2h to obtain a NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam, and store it for standby under the condition of isolating oxygen.
[0058] Figure 1 This is a scanning electron microscope image (SEM) of the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained in Example 1. It can be seen that the NiCoMoZnCu high entropy alloy nanoflower array is composed of multiple two-dimensional nanosheets, and the two-dimensional nanosheets have different orientations, and the two-dimensional nanosheets are perpendicular to the cobalt foam substrate, constructing a stable nanoflower array structure. It is worth noting that the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained is collected after sufficient ultrasonic treatment, so the dense nanoflower array indicates that the NiCoMoZnCu high entropy alloy nanoflower array is tightly bound to the cobalt foam substrate.
[0059] Figure 2 It is a high-resolution transmission electron microscopy image (HRTEM) of the NiCoMoZnCu high-entropy alloy nanoflower array obtained in Example 1, which further confirms that each nanoflower is composed of multiple two-dimensional nanosheets, constructing a three-dimensional (3D) porous nanostructure with a large specific surface area.
[0060] Figure 3 This is the X-ray diffraction (XRD) pattern of the NiCoMoZnCu high entropy alloy nanoflower array obtained in Example 1. No obvious diffraction peaks of other impurities were observed. At the same time, compared with the diffraction peaks characterizing pure Co, Ni, Mo, Zn and Cu, the diffraction peaks of the catalytic material obtained in Example 1 had an obvious shift, indicating that the NiCoMoZnCu high entropy alloy nanoflower array with a single-phase structure was successfully synthesized.
[0061] Figure 4 This is the atomic structure characterization diagram of the NiCoMoZnCu high entropy alloy nanoflower obtained in Example 1. It can be clearly seen that the five atoms of Co, Ni, Mo, Zn and Cu are evenly dispersed in the bright sublattice, which further indicates that the NiCoMoZnCu high entropy alloy nanoflower with a single-phase structure has been successfully synthesized.
[0062] Figure 5 This is the element distribution map (Mapping) of the NiCoMoZnCu high entropy alloy nanoflower obtained in Example 1, which clearly shows that the five elements Co, Ni, Mo, Zn and Cu are evenly distributed in the high entropy alloy nanoflower without phase separation.
[0063] Figure 6 This is the result of inductively coupled plasma elemental analysis (ICP) of the NiCoMoZnCu high entropy alloy nanoflower array obtained in Example 1. It can be seen that the atomic percentages of the five metal atoms are Co:Ni:Mo:Zn:Cu=59%:27%:7%:5%:2%. The sum of the atomic percentages of the five metal atoms is 100%.
[0064] Figure 7 7a and 7b are the linear voltammetry (LSV) test curves of the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained in Example 1, the cobalt foam substrate of Example 1 and commercial Pt / C as electrode materials for hydrogen evolution reaction and hydrazine oxidation reaction. The electrolyte used in the hydrogen evolution reaction is a 1.0 mol / L potassium hydroxide solution. The electrolyte used in the hydrazine oxidation reaction is a 1.0 mol / L potassium hydroxide solution containing 0.3 mol / L hydrazine hydrate (N2H4). Figure 7It can be seen that the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 1 has a better catalytic performance than the simple cobalt foam substrate and commercial Pt / C. For the hydrogen evolution reaction, it only requires a lower overpotential of 242.9mV and 307.5mV to reach 500mA cm -2 and 1000mA cm -2 The current density of the hydrazine oxidation reaction is better than that of the foamed cobalt substrate (635.2 mV and 684.9 mV) and commercial Pt / C (365.5 mV and 437.5 mV). For the hydrazine oxidation reaction, it only requires a lower working potential of -18.6 mV and 16.9 mV to reach 500 mA cm -2 and 1000mA cm -2 In contrast, the foamed cobalt substrate and commercial Pt / C require higher working potentials of 162.5 mV and 103.2 mV, respectively, to reach a current density of 500 mA cm -2 This proves that the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam of the present invention has excellent catalytic performance for hydrogen evolution reaction and hydrazine oxidation reaction.
[0065] Figure 8 The double layer capacitance (C) of NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 1 and commercial Pt / C as electrode materials at different scan rates dl ) value. dl The values can be obtained using cyclic voltammetry (CV) and the electrochemically active area (ECSA) can be evaluated. Figure 8 It can be seen that the C dl Value up to 268.8mF cm -2 , which greatly exceeds the commercial Pt / C electrode. This shows that the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam has an ultra-high effective electrochemical area. The main reason is that the loading amount of NiCoMoZnCu high entropy alloy nanoflower array grown on the cobalt foam substrate can reach 5.8mg.
[0066] Fig. 9 a and 9b are the Nyquist curves of the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 1, the cobalt foam substrate of Example 1 and commercial Pt / C for hydrogen evolution reaction and hydrazine oxidation reaction. In contrast, the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam has a smaller charge transfer resistance (R ct), which further confirmed that the NiCoMoZnCu high-entropy alloy nanoflower arrays supported by cobalt foam have faster hydrogen evolution reaction and hydrazine oxidation reaction kinetics at the electrolyte / catalyst interface.
[0067] Fig.10 a and 10b are the chronoamperometric curves (it) of the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam and commercial Pt / C for hydrogen evolution reaction and hydrazine oxidation reaction obtained in Example 1. It can be seen that for hydrogen evolution reaction, at 100 mA cm -2 At a current density of 50 mA cm, the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam in Example 1 can operate stably for 55 hours and maintain 98.2% of the initial current density. In contrast, the commercial Pt / C electrode can only maintain 73.4% of the initial current density after 15 hours of operation. For the hydrazine oxidation reaction, at 50 mA cm -2 At a current density of , the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam of Example 1 can maintain 96.8% of the initial current density after 50 hours of continuous testing, while the commercial Pt / C electrode can only maintain 65.6% of the initial current density after 7 hours of testing. The above results indicate that the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained by the present invention has super stability to hydrogen evolution reaction and hydrazine oxidation reaction.
[0068] Fig.11 a and 11b are the LSV performance comparisons of the hydrazine oxidation-assisted hydrogen production (OHzS) and water electrolysis (OWS) systems composed of various electrodes.
[0069] in, Fig.11 a is a comparison of the LSV performance of the OHzS system composed of the foam cobalt-loaded NiCoMoZnCu high entropy alloy nanoflower array of Example 1 and commercial Pt / C as cathode and anode catalysts.
[0070] Fig.11 b is the LSV performance comparison of the OHzS and OWS systems composed of the foam cobalt loaded NiCoMoZnCu high entropy alloy nanoflower array of Example 1 as both cathode and anode catalysts.
[0071] The electrolyte used in the above OHzS system is a 1.0 mol / L potassium hydroxide solution containing 0.2 mol / L hydrazine hydrate (N2H4). All electrolytes in the OWS system are 1.0 mol / L potassium hydroxide solutions. Fig.10In a, it can be seen that the OHzS system composed of the NiCoMoZnCu high entropy alloy nanoflower array supported by the cobalt foam of Example 1 as the cathode and anode catalysts only requires a battery voltage of 0.081, 0.260, and 0.376 V to reach 100, 500, and 1000 mA cm -2 The current density can reach 2000mA cm at a lower cell voltage of 0.646V. -2 The current density of OHzS system composed of commercial Pt / C as cathode and anode catalyst can only reach 622.5 mA cm at the same voltage. -2 This indicates that the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam in Example 1 has extremely high intrinsic activity for the OHzS system. Fig.10 As can be seen in b, for the OWS system composed of the NiCoMoZnCu high entropy alloy nanoflower array supported by the cobalt foam of Example 1 as the cathode and anode catalysts, it requires higher battery voltages of 1.729, 1.885, and 1.975 V to reach 100, 500, and 1000 mA cm -2 This shows that compared with the NiCoMoZnCu high entropy alloy nanoflower array material supported by cobalt foam in Example 1 of the OWS system, the efficient production of hydrogen in the OHzS system has an absolute advantage.
[0072] Fig.12 This is the chronoamperometric curve (it) of the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam for the OHzS system of Example 1. It can be seen that the OHzS system composed of the NiCoMoZnCu high entropy alloy nanoflower array can be -2 It can run stably for 300h at a current density of 1.58kWh, showing super stability.
[0073] Example 2
[0074] The high entropy alloy nanoflower arrays were prepared by the following steps
[0075] Step a: (NH4)6Mo7O 24 4H2O and CO(NH2)2 were placed in a 100mL reactor, 40mL of deionized water was added and ultrasonically dissolved to obtain a first mixed solution such that (NH4)6Mo7O 24 The concentration of 4H2O is 0.03 mol / L, and the concentration of CO(NH2)2 is 0.38 mol / L.
[0076] Step b, add Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O to the first mixed solution, and mix by ultrasonic to obtain a second mixed solution; the added amounts of the water-soluble cobalt salt, water-soluble nickel salt, water-soluble copper salt, and water-soluble zinc salt are 0.04 mol / L, 0.04 mol / L, 0.02 mol / L, and 0.01 mol / L, respectively, in a molar volume ratio to the first mixed solution.
[0077] Step c, place a 2cm×4cm cobalt foam in 40mL of 6 mol / L HCl solution, ultrasonically treat for 3min, then use deionized water and ethanol to ultrasonically clean the cobalt foam three times, then blow dry the cobalt foam, put it into the above-mentioned 100mL reactor, immerse it completely in the solution, close the reactor, move the reactor into a blast oven, and react at 120°C for 8h. After the reaction is completed, take out the cobalt foam with the sample, use deionized water and ethanol to ultrasonically clean it three times, put it into a blast oven after cleaning, and dry it at 80°C for 8h to obtain 0.12g NiCoMoZnCu high entropy alloy nanoflower array precursor loaded with cobalt foam;
[0078] Step d, pour 36mL of ethylene glycol solution containing 0.06 mol / L sodium borohydride and 0.7 mol / L sodium hydroxide into a 50mL reactor, and then put 0.12g of high entropy alloy nanoflower array precursor obtained in step c into the reactor (the mass ratio of the sodium borohydride to the high entropy alloy nanoflower array precursor is 1:1.5), so that it is completely immersed in the solution, the reactor is closed, and the reactor is moved into a blast oven and reacted at 160°C for 12h. After the reaction is completed, take out the reduced sample, use deionized water and ethanol to ultrasonically clean it three times, and after cleaning, put it into a vacuum drying oven and dry it at 60°C for 2h to obtain a NiCoMoZnCu high entropy alloy nanoflower array loaded with foam cobalt, and store it for standby under the condition of isolating oxygen.
[0079] Fig.13 This is a high-resolution transmission electron microscopy image (HRTEM) of the NiCoMoZnCu high-entropy alloy nanoflower array obtained in Example 2. It can be seen that each nanoflower is composed of multiple two-dimensional nanosheets, constructing a three-dimensional (3D) porous nanostructure with a large surface area.
[0080] Fig.14 This is the element distribution map (Mapping) of the NiCoMoZnCu high entropy alloy nanoflower obtained in Example 2, which clearly shows that the five elements Co, Ni, Mo, Zn and Cu are evenly distributed in the high entropy alloy nanoflower without phase separation.
[0081] Fig.15 This is the result of the inductively coupled plasma elemental analysis (ICP) of the NiCoMoZnCu high entropy alloy nanoflower array obtained in Example 2. It can be seen that the atomic percentages of the five metal atoms are Co:Ni:Mo:Zn:Cu=56.6%:29.8%:6.9%:6.0%:0.7%. Among the five metal atomic percentages, the highest content is close to 60%, and the lowest content is close to 0.5%. This proves that by adjusting the amount of metal salt added, the content of each element in the high entropy alloy nanoflower array can be regulated, and the atomic percentages of Co atoms, Ni atoms, Mo atoms, Zn atoms and Cu atoms are all 0.5% to 60%.
[0082] Fig.16 a and 16b are the linear voltammetry (LSV) test curves of the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained in Example 2 as an electrode material for hydrogen evolution reaction and hydrazine oxidation reaction. The electrolyte used in the hydrogen evolution reaction is a 1.0 mol / L potassium hydroxide solution. The electrolyte used in the hydrazine oxidation reaction is a 1.0 mol / L potassium hydroxide solution containing 0.1 mol / L hydrazine hydrate (N2H4). Fig.16 As can be seen in a, for the hydrogen evolution reaction, only relatively low overpotentials of 65.6 and 151.3 mV are required to reach 10 and 100 mA cm, respectively. -2 The current density is Fig.16 As can be seen in b, for the hydrazine oxidation reaction, only low working potentials of -61.8 and -9.1 mV are required to achieve 10 and 100 mA cm -2 of current density.
[0083] Example 3
[0084] The high entropy alloy nanoflower arrays were prepared by the following steps
[0085] Step a: (NH4)6Mo7O 24 4H2O and CO(NH2)2 were placed in a 100mL reactor, 40mL of deionized water was added and ultrasonically dissolved to obtain a first mixed solution such that (NH4)6Mo7O 24 The concentration of 4H2O is 0.03 mol / L, and the concentration of CO(NH2)2 is 0.45 mol / L.
[0086] Step b, add Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O to the first mixed solution, and mix by ultrasonication to obtain a second mixed solution; the added amounts of the water-soluble cobalt salt, water-soluble nickel salt, water-soluble copper salt, and water-soluble zinc salt are 0.02 mol / L, 0.04 mol / L, 0.01 mol / L, and 0.004 mol / L, respectively, in a molar volume ratio to the first mixed solution.
[0087] Step c, place a 2cm×4cm cobalt foam in 40mL of 6 mol / L HCl solution, ultrasonically treat for 3min, then use deionized water and ethanol to ultrasonically clean the cobalt foam three times, then blow dry the cobalt foam, put it into the above-mentioned 100mL reactor, immerse it completely in the solution, close the reactor, move the reactor into a blast oven, and react at 120°C for 8h. After the reaction is completed, take out the cobalt foam with the sample, use deionized water and ethanol to ultrasonically clean it three times, put it into a blast oven after cleaning, and dry it at 80°C for 8h to obtain 0.08g NiCoMoZnCu high entropy alloy nanoflower array precursor loaded with cobalt foam;
[0088] Step d, pour 36mL of ethylene glycol solution containing 0.04 mol / L sodium borohydride and 0.3 mol / L sodium hydroxide into a 50mL reactor (the mass ratio of the sodium borohydride to the high entropy alloy nanoflower array precursor is 1:1.5), and then put the high entropy alloy nanoflower array precursor obtained in step c into the reactor, so that it is completely immersed in the solution, close the reactor, move the reactor into a blast oven, and react at 140°C for 12h. After the reaction is completed, take out the reduced sample, use deionized water and ethanol to ultrasonically clean it three times, and after cleaning, put it into a vacuum drying oven and dry it at 60°C for 2h to obtain a NiCoMoZnCu high entropy alloy nanoflower array loaded with foam cobalt, and store it for standby under the condition of isolating oxygen.
[0089] Fig.17 This is a scanning electron microscope image (SEM) of the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained in Example 3. It can be seen that after adjusting the amount of metal salt added, its morphology structure is still a nanoflower array structure.
[0090] Fig.1818a and 18b are the linear voltammetry (LSV) test curves of the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained in Example 3 as an electrode material for hydrogen evolution reaction and hydrazine oxidation reaction. The electrolyte used in the hydrogen evolution reaction is a 1.0 mol / L potassium hydroxide solution. The electrolyte used in the hydrazine oxidation reaction is a 1.0 mol / L potassium hydroxide solution containing 0.1 mol / L hydrazine hydrate (N2H4). Fig.18 As can be seen in a, for the hydrogen evolution reaction, only relatively low overpotentials of 66.2 and 140.8 mV are required to achieve 10 and 100 mA cm, respectively. -2 The current density is Fig.18 As can be seen in b, for the hydrazine oxidation reaction, only low working potentials of -60.5 and -14.1 mV are required to achieve 10 and 100 mA cm -2 of current density.
[0091] Example 4
[0092] The high entropy alloy nanoflower arrays were prepared by the following steps
[0093] Step a: (NH4)6Mo7O 24 4H2O and CO(NH2)2 were placed in a 100mL reactor, 40mL of deionized water was added and ultrasonically dissolved to obtain a first mixed solution such that (NH4)6Mo7O 24 The concentration of 4H2O is 0.01 mol / L and the concentration of CO(NH2)2 is 0.25 mol / L.
[0094] Step b, adding Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O, and Cu(NO3)2·3H2O to the first mixed solution, and ultrasonically mixing to obtain a second mixed solution; the added amounts of the water-soluble cobalt salt, water-soluble nickel salt, water-soluble copper salt, and water-soluble zinc salt are 0.04 mol / L, 0.025 mol / L, 0.01 mol / L, and 0.004 mol / L, respectively, in a molar volume ratio to the first mixed solution.
[0095] Step c, place a 2cm×4cm cobalt foam in 40mL of 6 mol / L HCl solution, ultrasonically treat for 3min, then use deionized water and ethanol to ultrasonically clean the cobalt foam three times, then blow dry the cobalt foam, put it into the above-mentioned 100mL reactor, immerse it completely in the solution, close the reactor, move the reactor into a blast oven, and react at 80°C for 12h. After the reaction is completed, take out the cobalt foam with the sample, use deionized water and ethanol to ultrasonically clean it three times, put it into a blast oven after cleaning, and dry it at 80°C for 8h to obtain 0.06g NiCoMoZnCu high entropy alloy nanoflower array precursor loaded with cobalt foam;
[0096] Step d, pour 36mL of ethylene glycol solution containing 0.03 mol / L sodium borohydride and 0.4 mol / L sodium hydroxide into a 50mL reactor, and then put the high entropy alloy nanoflower array precursor obtained in step c into the reactor (the mass ratio of the sodium borohydride to the high entropy alloy nanoflower array precursor is 1:1.5), so that it is completely immersed in the solution, the reactor is closed, and the reactor is moved into a blast oven and reacted at 140°C for 8h. After the reaction is completed, take out the reduced sample, use deionized water and ethanol to ultrasonically clean it three times, and after cleaning, put it into a vacuum drying oven and dry it at 60°C for 2h to obtain a NiCoMoZnCu high entropy alloy nanoflower array loaded with foam cobalt, and store it for standby under the condition of isolating oxygen.
[0097] Fig.19 This is a scanning electron microscope image (SEM) of the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained in Example 4. It can be seen that after adjusting the amount of metal salt added and the composition of the reducing agent, its morphology structure is still a nanoflower array structure.
[0098] Fig. 20 20a and 20b are the linear voltammetry (LSV) test curves of the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained in Example 4 as an electrode material for hydrogen evolution reaction and hydrazine oxidation reaction. The electrolyte used in the hydrogen evolution reaction is a 1.0 mol / L potassium hydroxide solution. The electrolyte used in the hydrazine oxidation reaction is a 1.0 mol / L potassium hydroxide solution containing 0.1 mol / L hydrazine hydrate (N2H4). Fig. 20 As can be seen in a, for the hydrogen evolution reaction, only relatively low overpotentials of 75.3 and 167.2 mV are required to achieve 10 and 100 mA cm, respectively. -2 The current density is Fig. 20 As can be seen in b, for the hydrazine oxidation reaction, only low working potentials of -43.3 and 14.9 mV are required to achieve 10 and 100 mA cm -2The experimental data shown in the accompanying drawings fully demonstrate the excellent performance of the NiCoMoZnCu high entropy alloy nanoflower array catalyst of the present invention. Many of its physical and chemical properties have greatly surpassed the current commercial Pt / C catalyst. It is a major breakthrough in the field of high entropy alloy catalyst materials and has considerable prospects in practical applications.
[0099] Comparative Example 1
[0100] Referring to the method in Example 1, the foamed cobalt substrate was replaced with a foamed nickel substrate, and the other steps remained unchanged to obtain a high entropy alloy nanoflower array supported by the foamed nickel substrate. The loading amount of the high entropy alloy nanoflower array grown on the foamed nickel substrate was 1 mg.
[0101] Fig.21 The linear voltammetry (LSV) test curves of the catalyst material obtained in Example 1 and the NiCoMoZnCu high entropy alloy nanoflower array loaded with cobalt foam obtained in Example 1 for hydrogen evolution reaction. The electrolytes used were 1.0 mol / L potassium hydroxide solution. Fig.21 As can be seen in the figure, for the hydrogen evolution reaction, the NiCoMoZnCu high entropy alloy nanoflower array grown on the foamed cobalt substrate in Example 1 only needs a relatively low overpotential of 63.1 and 139.6 mV to reach 10 and 100 mA cm -2 The current density is better than that of the material obtained in Comparative Example 1 (79.8 mV) and 167.6 mV). The main reason is that the loading amount (1 mg) of the nickel foam substrate is much lower than that of the cobalt foam substrate (5.8 mg), which makes it have a lower electrochemical specific surface area, thereby leading to a decrease in catalytic activity. This shows that the selection of cobalt foam as the substrate in this application has unexpected technical effects.
[0102] Comparative Example 2
[0103] Referring to the method in Example 1, the concentration of sodium borohydride in the ethylene glycol solution was changed to 0.35 mol / L.
[0104] Fig. 22 This is a scanning electron microscope (SEM) image of the catalytic material obtained in Comparative Example 2. It can be seen that when the concentration of sodium borohydride is increased, the high entropy alloy nanoflower array structure collapses and the overall morphology is granular.
[0105] Comparative Example 3
[0106] See the method in Example 1, (NH4)6Mo7O 24 ·4H2O no longer dissolves alone, but dissolves with other metal salts by ultrasonication.
[0107] The specific method is as follows:
[0108] The high entropy alloy nanoflower array material is prepared by the following steps:
[0109] Step a: 1.07 mmol (NH4)6Mo7O 24 ·4H2O, 1.5mmolCo(NO3)2·6H2O, 1.5mmolNi(NO3)2·6H2O, 0.9mmolZn(NO3)2·6H2O, 0.75mmolCu(NO3)2·3H2O, and 18mmol CO(NH2)2 were placed in a 100mL reactor, 40mL of deionized water was added and dissolved by ultrasonication to obtain a mixed solution;
[0110] Step b, place a 2cm×4cm cobalt foam in 40mL of 6MHCl solution, ultrasonically treat for 3min, then use deionized water and ethanol to ultrasonically clean the cobalt foam three times, then blow dry the cobalt foam, put it into the above-mentioned 100mL reactor, immerse it completely in the solution, close the reactor, move the reactor into a blast oven, and react at 120°C for 12h. After the reaction is completed, take out the cobalt foam with the sample, use deionized water and ethanol to ultrasonically clean it three times, put it into a blast oven after cleaning, and dry it at 80°C for 8h to obtain a NiCoMoZnCu high entropy alloy nanoflower array precursor loaded with cobalt foam;
[0111] Step c, pour 36mL of ethylene glycol solution containing 0.07M sodium borohydride and 0.8M sodium hydroxide into a 50mL reactor, and then put the high entropy alloy nanoflower array precursor obtained in step c into the reactor, so that it is completely immersed in the solution, close the reactor, move the reactor into a blast oven, and react at 160°C for 12h. After the reaction is completed, take out the reduced sample, use deionized water and ethanol to ultrasonically clean it three times, and after cleaning, put it into a vacuum drying oven and dry it at 60°C for 2h to obtain a catalytic material, and store it for standby under the condition of isolating oxygen.
[0112] Fig.23 The linear voltammetry (LSV) test curves of the catalyst material obtained in Example 3 and the NiCoMoZnCu high entropy alloy nanoflower array supported by cobalt foam obtained in Example 1 for hydrogen evolution reaction. The electrolytes used were 1.0 mol / L potassium hydroxide solution. It can be seen that when (NH4)6Mo7O 24 When 4H2O was dissolved with other metal salts, the catalytic performance of the obtained materials deteriorated, requiring lower overpotentials of 201.5 and 304.7 mV to reach 10 and 100 mA cm, respectively. -2The NiCoMoZnCu high entropy alloy nanoflower array grown on the cobalt foam substrate in Example 1 only needs a lower overpotential of 63.1 and 139.6 mV to reach 10 and 100 mA cm -2 The main reason is that (NH4)6Mo7O 24 When 4H2O is dissolved together with other metal salts, insoluble precipitates will be produced, which will affect the growth of high entropy alloy nanoflower arrays on the cobalt foam substrate, thereby causing its catalytic performance to deteriorate.
Claims
1. A high entropy alloy nanoflower array material, characterized in that: The high entropy alloy nanoflower array material comprises: a foamed cobalt substrate and a high entropy alloy nanoflower array loaded on the foamed cobalt substrate, wherein the high entropy alloy nanoflower array is composed of five metal elements: Co, Ni, Mo, Zn, and Cu; In the high entropy alloy nanoflower array, the atomic percentages of Co atoms, Ni atoms, Mo atoms, Zn atoms and Cu atoms are all 0.5% to 60%.
2. A method for preparing the high entropy alloy nanoflower array material according to claim 1, comprising the following steps: Step a, placing a water-soluble molybdenum salt and a precipitant in a reaction container, adding water and dissolving them to obtain a first mixed solution; Step b, adding a water-soluble cobalt salt, a water-soluble nickel salt, a water-soluble copper salt, and a water-soluble zinc salt to the first mixed solution, mixing to obtain a second mixed solution; Step c, placing the foamed cobalt into the above reaction container, sealing the reaction container, and reacting the reaction container at 80-120° C. for 8-12 hours to obtain a foamed cobalt-loaded high entropy alloy nanoflower array precursor; Step d, placing the reducing agent and the cobalt foam-loaded high entropy alloy nanoflower array precursor obtained in step c into a reaction container, sealing the reaction container, and reacting at 140-160° C. for 8-12 hours to obtain a cobalt foam-loaded high entropy alloy nanoflower array.
3. The method for preparing the high entropy alloy nanoflower array material according to claim 2, characterized in that: The water-soluble molybdenum salt in step a is (NH4)6Mo7O 24 ·4H2O, the precipitant is CO(NH2)2.
4. The method for preparing a high entropy alloy nanoflower array according to claim 2, wherein: In step d, the reducing agent is an ethylene glycol solution containing sodium borohydride and sodium hydroxide, wherein the concentration of sodium hydroxide in the ethylene glycol solution is 0.3-0.8 mol / L, and the concentration of sodium borohydride in the ethylene glycol solution is 0.03-0.07 mol / L.
5. The method for preparing a high entropy alloy nanoflower array according to claim 2, characterized in that: In the first mixed solution, the concentration of the water-soluble molybdenum salt is 0.01-0.03 mol / L, and the concentration of the precipitant is 0.25-0.45 mol / L.
6. The method for preparing a high entropy alloy nanoflower array according to claim 2, characterized in that: The molar volume ratios of the added amounts of the water-soluble cobalt salt, the water-soluble nickel salt, the water-soluble zinc salt and the water-soluble copper salt to the first mixed solution are: 0.02-0.04 mol / L, 0.025-0.04 mol / L, 0.01-0.02 mol / L and 0.004-0.02 mol / L respectively.
7. Use of the high entropy alloy nanoflower array material according to claim 1 for catalyzing hydrogen evolution reaction.
8. Use of the high entropy alloy nanoflower array material according to claim 1 for catalyzing hydrazine oxidation reaction.
9. Use of the high entropy alloy nanoflower array material according to claim 1 as a cathode and / or anode material of a hydrazine oxidation-assisted hydrogen production system.
Citation Information
Patent Citations
Preparation method of medium-high entropy alloy nanoflower catalyst
CN116666633A
Seed layer induced FeCoNiCuMo high-entropy alloy nanocage electrocatalyst as well as preparation method and application thereof
CN119187590A